1991
DOI: 10.1038/ki.1991.63
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of tubulointerstitial fibrosis

Abstract: With regard to tubulointerstitial fibrogenesis we are left with a variety informational gaps regarding nearly all aspects of this clinically important process. Table 2 summarizes a generalized version of fibrogenesis based primarily on investigations in other organs. Extrapolation of data obtained with other fibrogenic systems is useful, but only in so far as it motivates us to adapt and test many of the experimental principles within in the context of the kidney. This begins with a comprehensive examination o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
166
0
14

Year Published

1992
1992
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 275 publications
(182 citation statements)
references
References 52 publications
2
166
0
14
Order By: Relevance
“…Furthermore, TGF-β modulates the expression of integrins, which are cell-surface receptors for ECM components, thereby facilitating cell adhesion and matrix deposition [39,40]. TGF-β also acts on (myo)fibroblasts, which are the main source of the increased ECM deposition in tissue fibrosis: TGF-β is a chemoattractant for fibroblasts [41], stimulates fibroblast proliferation [42], and regulates transdifferentiation of resident kidney cells into myofibroblasts [43].…”
Section: Transforming Growth Factor-betamentioning
confidence: 99%
“…Furthermore, TGF-β modulates the expression of integrins, which are cell-surface receptors for ECM components, thereby facilitating cell adhesion and matrix deposition [39,40]. TGF-β also acts on (myo)fibroblasts, which are the main source of the increased ECM deposition in tissue fibrosis: TGF-β is a chemoattractant for fibroblasts [41], stimulates fibroblast proliferation [42], and regulates transdifferentiation of resident kidney cells into myofibroblasts [43].…”
Section: Transforming Growth Factor-betamentioning
confidence: 99%
“…This may partially be attributed to the fact that it was long considered the exclusive domain of descriptive ultrastructural research, which implied that the interstitium was mostly a passive tissue that structurally supported the tubular epithelium (1,2). The renal interstitium received increasing interest in the context of kidney abnormalities, when the role of interstitial fibrosis in progression of CKD became obvious (3)(4)(5). Only since transgenic animal studies revealed the physiologic endocrine function of interstitial cells as sources of erythropoietin (Epo) and renin has the physiologic role of the renal interstitium received its due attention.…”
Section: Introductionmentioning
confidence: 99%
“…Renal interstitial fibrosis develops following renal tubular and glomerular injury (4,19,31,35,37,45). The fibrotic lesion is evoked through complex pathologic processes, requiring participation of various inflammatory cells and abnormal accumulation of extracellular matrices (ECM) (5,7,9,19,35,39).…”
Section: Introductionmentioning
confidence: 99%